Pengelolaan Daerah Aliran Sungai (DAS) Lematang Ulu Terpadu : Tinjauan Literatur - Nurqutni Nurqutni; Reflis Reflis; Bambang Sulstyo; Sukisno Sukisno (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
A river basin (DAS) is an area bordered by mountain ridges where rainwater that falls on the area will be collected by the mountain ridges and will be channeled through small rivers to the main river (Asdak, 1995). A watershed includes a land area which is one unit with a river and its tributaries, which functions to accommodate, store and channel water originating from rainfall to a lake or to the sea naturally, where the boundary on land is a topographical divide and the boundary at sea is up to with water areas that are still affected by land activities. The Lematang River is one of the longest rivers in South Sumatra, the length of the Lematang River is 271 km with a watershed area (DAS) of 295.88 km2. The existence of the Lematang watershed is a source of life for the Lahat community. The decline in the carrying capacity and carrying capacity of the Lematang watershed due to land use can be seen from flash floods and landslides, where flash floods bring sedimentation, logs of wood and twigs causing losses to the community. To overcome the problems of the Lematang Ulu watershed, Integrated Watershed Management is needed by taking concrete steps in the form of efforts to formulate goals, synchronize programs, implement and control watershed resource management across stakeholders in a participatory manner based on studies of biophysical, economic, social, political and institutional conditions in order to realize the goals. Watershed Management.